Improving Teacher’s Performance Through Principal’s Leadership - Sandika, Rinaldy; Lian, Bukman; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2022)
The purpose of this research is to describe the principal's leadership in enhancing teacher performance at SD Negeri 6 Mendo Barat. This study employs a descriptive qualitative technique. This study's informants included six principals, instructors, and school managers. Interviews, observation, and documentation are used as data collecting approaches. Using triangulation techniques, assess the data's veracity. The findings revealed that: 1) principal leadership has an effect on improving teacher performance as evidenced by providing motivation to work, fostering discipline, rewarding, consulting, conducting class visits, demonstrating exemplary attitudes and behavior, and developing the teaching profession; 2) the instructor's performance is well established, as indicated by the teacher preparing a lesson plan, organizing learning activities, developing interpersonal relationships, performing assessments, following up on assessment findings, and mastering academic subjects. The study's findings indicate that the principal's leadership is important in increasing teacher effectiveness and contributing to the advancement of learning quality.